Non-invasive prenatal screening in three cases of vanishing twin syndrome and a literature review - Shu, Xinni; Yang, Jiexia; Wang, Yousheng; Zhang, Zhuanping; Guo, Fangfang; Peng, Haishan; Wang, Dongmei; Hou, Yaping (Zhonghua yi xue yi chuan xue za zhi, 2025)
To assess the impact of vanishing twin syndrome (VTS) on the accuracy of non-invasive prenatal testing (NIPT). Three pregnant women who underwent NIPT testing at Guangdong Women and Children's from November 2019 to February 2020 were selected as the study subjects. The three women had either vanish twin syndrome or had undergone fetal reduction for other reasons in one of their twins, and were subsequently subject to NIPT, chromosome karyotyping, chromosome microarray analysis (CMA), and short tandem repeat (STR) analysis. This study has been approved by the Medical Ethics Committee of Guangdong Maternal and Child Health Hospital (Ethics No.: 20230132). Case 1 underwent selective fetal reduction at 8 weeks of gestation. At 17 weeks, NIPT showed a fetal DNA fraction of 2.806%, with results indicating the presence of Y chromosome and abnormal sex chromosome ratios. However, the women had subsequent uncomplicated vaginal delivery of a female infant, and no abnormality noted. Case 2 experienced spontaneous demise